Resilience of Hydrobia ulvae populations to anthropogenic and natural disturbances - Cardoso, P. G. (2005)
In the Mondego estuary (Portugal), several mitigation measures (nutrient loading reduction, seagrass bed protection and freshwater circulation enhancement) were implemented in 1998 to promote the recovery of the seagrass bed and the entire surrounding environment following a long period of eutrophication. In the present study we evaluate the success of this restoration project, by comparing the water nutrient concentrations, the seagrass-cover extent and the dynamics of Hydrobia ulvae, before and after implementation of the management measures. During the period in which environmental quality declined, H. ulvae abundance, biomass and growth production declined, associated with the almost total disappearance of the macrophyte Zostera noltii. However, after the implementation of management measures, dissolved nutrients and green macroalgal blooms were much reduced, and the seagrass bed started to recover. The H. ulvae population also responded positively, becoming more structured (including individuals of all age classes), with higher abundance and biomass. Major flood events demonstrated that the resilience of the H. ulvae population may have been lowered by the original chronic stressor (eutrophication). The population structure of H. ulvae in the most stressed site continued to be dominated by small individuals despite the improvements in water quality, probably a result of the absence of seagrass plants at this site. Estuarine restoration programmes need to recognise the importance of understanding the resilience of populations and the interactions of multiple stressors